Pola Resistensi Bakteri Penyebab Infeksi Saluran Kemih (ISK) pada Pasien di Salah Satu Rumah Sakit Swasta di Jakarta Utara Periode 2019-2021 - Maulin Inggraini; Reza Anindita; Euodia Naomi Septiana Siburian; Noor Andryan Ilsan (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
Urinary Tract Infection (UTI) is an infectious disease of the urinary tract caused by bacteria. Treatment therapy for UTI is done by giving antibiotics. However, the use of antibiotics often poses a risk of bacterial resistance that causes UTIs which has an impact on increasing morbidity rates, resulting in high UTI treatment costs. This study aims to determine the pattern of UTI bacterial resistance to antibiotics in UTI patients at a private hospital in North Jakarta for the 2019-2021 period. Cross sectional design, using a non-analytic retrospective approach conducted at a private hospital in North Jakarta for the 2019-2021 period. The sample of this study was secondary data totaling 159 urine of UTI patients taken by purposive sampling. The data is processed in tabular form and described to see a picture of UTI patients in a private hospital in North Jakarta for the 2019-2021 period. The results showed that there were more female UTI patients (68%) than men (32%), the most common bacteria causing UTI was E. colli (61.64%), the dominant antibiotic causing UTI bacterial resistance was ampicillin (67.92%). The conclusion of this study is that E. coli is the most dominant cause of UTI and ampicillin is the antibiotic that causes the most resistance to UTI bacteria.